Locational aspects of foreign direct investment in Portugal - Pontes, José Pedro (2021)
The paper deals with the evolution of foreign direct investment (henceforth named FDI) in a host country in what concerns the location aspect: why is a good produced in a country by a foreign subsidiary instead of being imported from the mother-firm? Following the "new economic geography" strand of literature. The location of investment is explained by three forces: increasing returns, which tend to concentrate production in the large country; transport costs, which decentralize production most the more symmetric the distribution of population is; and comparative advantage following from immobile factors of production, which we assume to benefit the small country. Along a process of economic integration, the small country has in the beginning (with high transfer costs) an FDI directed to the local market. Then, with lower (intermediate) trade costs, the small country becomes dependent on imports. Eventually, with very low trade costs, it will be possible for the small country to exploit a comparative advantage and have an FDI addressed both to local and foreign markets. This methodology enables to explain three stylised facts of FDI in Portugal since adhesion to the European Community in 1986. First, it explains why FDI rose fast from 1986 up to 1991 and stagnated ever since. Then, it enables to understand the sensibility of FDI to conjuncture. At last, the reasons of the increasing magnitude of disinvestment by foreign firms in recent years can be understood